Building Resilient Regions: Complex Adaptive Systems and the Role of Policy Intervention - Bristow, Gillian; Healy, Adrian (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The notion of resilience is being utilised by an increasing number of authors keen to understand the dynamics of local and regional economies and particularly how they deal with economic shocks and recessionary crises. Within the burgeoning literature however, fairly limited attention has been paid to date to developing a robust conceptual understanding of what role policy-makers, particularly at sub-national level, might play in building economic resilience in regions. The purpose of this paper is to address this gap. Drawing on resilience literatures which employ a complex adaptive systems perspective, the paper seeks to develop a conceptual framework within which policy action, particularly at the subnational level, can be theorised and understood. It identifies three critical dimensions which frame the role and scope for policy intervention in the management of regional economic resilience: the modes and structures of governance, the types of policy interventions which help build resilience, and the horizons or timings for appropriate intervention. The paper concludes by considering what this framing means for the nature and scope of subnational policy intervention for regional economic resilience.